New Insights Into Permeation of Large Cations Through ATP-Gated P2X Receptors - Peverini, Laurie; Beudez, Juline; Dunning, Kate; Chataigneau, Thierry; Grutter, Thomas (Frontiers in Molecular Neuroscience, 2018)
The permeability of large cations through the P2X pore has remained arguably the most controversial and complicated topic in P2X-related research, with the emergence of conflicting studies on the existence, mechanism and physiological relevance of a so-called “dilated” state. Due to the important role of several “dilating” P2X subtypes in numerous diseases, a clear and detailed understanding of this phenomenon represents a research priority. Recent advances, however, have challenged the existence of a progressive, ATP-induced pore dilation, by demonstrating that this phenomenon is an artifact of the method employed. Here, we discuss briefly the history of this controversial and enigmatic dilated state, from its initial discovery to its recent reconsideration. We will discuss the literature in which mechanistic pathways to a large cation-permeable state are proposed, as well as important advances in the methodology employed to study this elusive state. Considering recent literature, we will also open the discussion as to whether an intrinsically dilating P2X pore exists, as well as the physiological relevance of such a large cation-permeable pore and its potential use as therapeutic pathway.